Serum podocalyxin levels in patients with obesity and carbohydrates disorders - Iveta Nedeva; Vera Karamfilova; Vlayko Vodenicharov; Antonina Gerganova; Tsvetelina Velikova; Yavor Assyov (Pensoft Publishers, 2024)
Background: Podocalyxin is expressed not only in glomerular podocytes but also on the endothelial cell surface outside the kidney. The aim of this cross-sectional study is to evaluate the role of serum podocalyxin as an early marker for vascular injury in patients with obesity and carbohydrate disturbances. Subjects and methods: The study group consisted of 163 patients with a mean age of 52.5 ± 11.3 years. Results: Levels of podocalyxin were significantly higher in healthy controls compared to patients with obesity, prediabetes, and newly diagnosed diabetes. Correlation analysis revealed that podocalyxin correlates negatively with BMI, waist circumference, waist-to-hip ratio, waist to stature ratio, fasting insulin, and one hour after the oral glucose tolerance test. ROC analyses determined that circulating podocalyxin levels are valuable for differentiating subjects with prediabetes and obesity. Conclusion: This study is the first to assess the role of podocalyxin in the entire spectrum of metabolic disorders.